Correction to: Comparing and assessing physical activity guidelines for children and adolescents: a systematic literature review and analysis - Anne-Maree Parrish; Mark S. Tremblay; Stephanie Carson; Sanne L. C. Veldman; Dylan Cliff; Stewart Vella; Kar Hau Chong; Maria Nacher; Borja del Pozo Cruz; Yvonne Ellis; Salome Aubert; Billie Spaven; et al. (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.